The Effect of Educational and Economic Deprivation on Fairtrade Coffee and Chocolate Purchasing - Blake, Ruairi; Harvey, John; Long, Gavin; Mansilla, Roberto; Brookes, Laurence; Deka, Lipika; Flick, Catherine (International Journal of Population Data Science, 2025)
Introduction & Background Ethical consumption has, generally, increased over the past 20 years in line with access to information. However, little research exists that explicitly ties access to information with ethical purchasing. What research does exist suggests a major obstacle to ethical purchasing is financial means, but this explanation leaves a “intention-behaviour gap” that is typically explained as a lack of moral motivation, but this may not be the case. Objectives & Approach The purpose of this study was to explore how key deprivation indicators, such as the Index of Multiple Deprivation (IMD), and IMD subdomains of Income and Education, affect one well-known, highly visible aspect of ethical purchasing: Fairtrade (specifically, chocolate and coffee products across all price points available in most stores). By utilising anonymised customer data from a major UK supermarket and mapping this data onto neighborhood-level deprivation scores, a probabilistic assessment of the effects of these areas of deprivation was carried out. Relevance to Digital Footprints By using transactional data from over 450,000 customer’s supermarket loyalty cards, this study shows how access to education may play a role in promoting ethical consumerism. This work was carried out with the goal of promoting a more environmentally and socially conscious type of consumption. Results Overall IMD and Income deprivation indices were inversely related to fairtrade purchasing up to the 5th decile of deprivation (i.e. most deprived areas purchased fewer Fairtrade products) before plateauing. Education deprivation showed an inverse relationship across all deciles, demonstrating that educational deprivation acts as a major predictor of Fairtrade purchasing even when the effect of income is kept separate. More educational access means more Fairtrade purchasing across coffee and chocolate products. Conclusions & Implications This analysis of real-world shopping data shows that educational deprivation, which can affect access to information, is a major factor that predicts ethical purchasing. Though we can’t infer causation, these findings suggest that organisations wishing to promote ethical consumption may benefit from addressing informational/educational roadblocks rather than assuming ethical consumption is just a problem of wealth and moral motivation.